1999
DOI: 10.1007/s004180050345
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of proliferative, cytoskeletal, and adhesive proteins during postnatal development of the hamster submandibular gland

Abstract: Although the submandibular gland (SMG) plays important exocrine and endocrine roles, little is known about the molecular details underlying its development. Previously, we reported that in the postnatally developing hamster SMG, GPT, the protein product of the first N-glycosylation gene, ALG7, was an in vivo marker for salivary cell proliferation. Here we investigated the proliferative, cytoskeletal, and adhesive changes during SMG postnatal development. The cellular localization and abundance of GPT, filament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 31 publications
(30 reference statements)
0
18
0
Order By: Relevance
“…DPAGT1 and protein N-glycosylation have been shown to be regulated with development and differentiation, and in response to cell density information, but the underlying mechanisms have remained obscure (Clark et al, 1983;Fernandes et al, 1999;Hayes and Lucas, 1983;Meissner et al, 1999;Mota et al, 1994;Welply et al, 1985). Here, using MDCK cells, we report that under normal physiological conditions, DPAGT1 senses cell density via canonical Wnt signaling and AJ maturity.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…DPAGT1 and protein N-glycosylation have been shown to be regulated with development and differentiation, and in response to cell density information, but the underlying mechanisms have remained obscure (Clark et al, 1983;Fernandes et al, 1999;Hayes and Lucas, 1983;Meissner et al, 1999;Mota et al, 1994;Welply et al, 1985). Here, using MDCK cells, we report that under normal physiological conditions, DPAGT1 senses cell density via canonical Wnt signaling and AJ maturity.…”
Section: Introductionmentioning
confidence: 64%
“…Since DPAGT1 has also been shown to be downregulated in growth arrested cells (Fernandes et al, 1999), we examined whether this was a direct consequence of reduced canonical Wnt activity. Analyses of DPAGT1 transcript levels by quantitative PCR revealed a 50% reduction in dense cells compared to sparse cultures (Fig.…”
Section: Dpagt1 Senses Cell Density Information Through Canonical Wntmentioning
confidence: 99%
“…Previous studies have indicated that salivary gland development entails temporal and spatial coordination among cell proliferation, cytoarchitectural organization, and the establishment of stable cell-substratum interactions (Fernandes et al 1999). However, the molecular mechanisms underlying these events are not known.…”
Section: Discussionmentioning
confidence: 99%
“…Protein N-glycosylation has been shown to be regulated with cell proliferation and differentiation (8,14,37). Thus, we reasoned that as a key regulator of N-glycosylation, the DPAGT1 gene is likely a downstream target of signaling pathways with roles in development.…”
Section: Dpagt1 Promoter Contains Tcf/lef-binding Sequences-mentioning
confidence: 99%
“…N-Glycosylation has been shown to be indispensable for development, and its dysregulation has been linked to various diseases, including cancer (3,4,10,11). Expression of DPAGT1, the gene that initiates the synthesis of the lipid-linked oligosaccharide precursor for protein N-glycosylation in the endoplasmic reticulum and is a key determinant of the extent of protein N-glycosylation (12,13), is down-regulated with cellular differentiation, suggesting that attenuation of N-glycosylation is required for the establishment of a differentiated phenotype (14). Indeed, recent studies have documented that DPAGT1 is an upstream regulator of N-glycosylation status of E-cadherin and that its diminished expression is required for the formation of mature intercellular adhesion complexes (15).…”
mentioning
confidence: 99%